Synchronized musical impact as recovery aid for sportsmen (marital arts) - Kolomiets, O. I.; Bykov, E. V.; Petrushkina, N. P. (The Russian Journal of Physical Education and Sport, 2017)
Annotation. The process of physical working capacity increase of a sportsman is conditioned not only by a correct volume of physical loads, but also by a correct organization of recovery, it means that recovery is an important part of a training process. The state of recovery is determined as activation decrease in an organism during rest and/or work. It is connected with the absence of outer and inner factors of stress and domination of parasympathetic activation. Speed of recovery after training and competitive loads depends not only on the regimen of rest and loads optimization, but also on the choice of recovery means. Material. The influence estimation of a synchronized musical impact on recovery processes of sportsmen during pre-competitive period. Research methods: scientific literature analysis and summarizing, Firstbeat-monitoring, questionnaire survey, experiment. Results. With the use of Firstbeat-monitoring during a sleep (480 minutes) several indices were determined, which characterize the processes of recovery (time of relax and time of stress, cardio-vascular activity and oxygen consumption indices, peculiarities of energy exchange and vegetative regulation). The quality of organism recovery during a sleep in the main group turned out to be validly better, than in the control group. More distinct vagal influence in the main group, prove a high index of recovery, low indices of maximum and minimum heart rate, oxygen consumption indices and the peculiarities of energy exchange, stated during a sleep. Conclusion. The results of a synchronized musical impact study during the training prove its positive influence on a sportsman`s recovery.